Beispiel Nr: 28
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(-2/0)\qquad Q(-4/0) \\\\ \\ \textbf{Rechnung:} \\ P(-2/0)\qquad Q(-4/0) \qquad a=-3 \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=-3(x+2)(x+4)\\ y=-3(x^2+x \cdot 2 +4\cdot x +2\cdot 4 )\\ y=-3(x^2 +6 x+8) \\ y= -3x^2-18x-24 $